From Arabic Literacy to Moderate Thinking: Designing Religious Moderation–Based Reading Instructional Materials in Indonesia - Achmad Fudhaili; Muhammad Najib (Prodi Pendidikan Bahasa Arab, Universitas Muhammadiyah Tangerang, 2026)
This study aims to design and evaluate Arabic reading instructional materials grounded in religious moderation, aligned with Indonesiaâ€™s Kurikulum Merdeka, to promote moderate religious understanding among intermediate learners. Using a Research and Development (R&D) approach, the study applies the ADDIE instructional design model, encompassing analysis, design, development, implementation, and evaluation. The needs analysis, conducted through classroom observations, interviews, and curriculum document reviews, revealed that Arabic reading instruction at the secondary level remains predominantly grammar-oriented and lacks systematic integration of religious moderation values. The developed materials integrate core principles of religious moderation, including tolerance (tasÄmuh), balance (iâ€˜tidÄl), deliberation (shÅ«rÄ), and peaceful coexistence, into contextual reading texts such as narratives, dialogues, and visual-based content. The materials align with the learning outcomes and character dimensions of the Merdeka Curriculum and incorporate multimodal features to support comprehension and engagement. Implementation results indicate significant improvements in studentsâ€™ reading achievement and moderate religious perspectives, demonstrating the effectiveness of value-based Arabic reading instruction.